Analysis of Student’s Difficulties in Solving Physics Problem: Impulse and Momentum Topics - Adianto, Tri; Rusli, Muhammad Aqil (Unnes Science Education Journal, 2021)
Physics education essentially intends to cultivate student’s analytical and reasoning capabilities. However, this objective is hard to achieve because there are many students who facing difficulties in solving physics problems. This research was conducted to identify the types of student’s difficulties in solving momentum and impulse problems, along with the factors causing it. This research was conducted using a descriptive qualitative approach to 66 students of Senior High School 2 Makassar who had studied momentum and impulse topics. The data collection process was carried out using test and interviews. Based on the results, it can be identified that there are two types of student’s difficulties in solving momentum and impulse problems. The first type was physical difficulties which consisted of student’s difficulty in understanding the questions (26%) and student’s difficulty in determining the useable equations (25%). Then, the second type was mathematical difficulties which consisted of student’s difficulty in substituting the data to the equation (63%) and student’s difficulty in performing mathematical operations (76%). Based on interviews and analysis, it can be concluded that these difficulties was commonly faced by students while solving physics problems, including in momentum and impulse topic. Futhermore, the difiiculties were caused by several factors, namely: 1) the lack of student’s understanding about physics concepts, 2) the weakness of student’s mathematical skills, 3) the lack of physics learning process which is not honing student’s problem-solving skills and 4) the lack of student’s motivation on developing their problems solving skills in physics subjects. Thus, researchers recommend to all physics teachers in Indonesia to immediately develop or implement learning strategies or methods which are considered capable of overcome all student’s difficulties that have been found.